Liver-Targeted Prodrugs of 2‘-C-Methyladenosine for Therapy of Hepatitis C Virus Infection - Hecker, Scott J; Reddy, K. Raja; van Poelje, Paul D; Sun, Zhili; Huang, Wenjian; Varkhedkar, Vaibhav; Reddy, M. Venkat; Fujitaki, James M; Olsen, David B; Koeplinger, Kenneth A; Boyer, Serge H; Linemeyer, David L; et al. (Journal of medicinal chemistry, 2007)
2‘-C-Methyladenosine exhibits impressive inhibitory activity in the cell-based hepatitis C virus (HCV) subgenomic replicon assay, by virtue of intracellular conversion to the corresponding nucleoside triphosphate (NTP) and inhibition of NS5B RNA-dependent RNA polymerase (RdRp). However, rapid degradation by adenosine deaminase (ADA) limits its overall therapeutic potential. To reduce ADA-mediated deamination, we prepared cyclic 1-aryl-1,3-propanyl prodrugs of the corresponding nucleoside monophosphate (NMP), anticipating cytochrome P450 3A-mediated oxidative cleavage to the NMP in hepatocytes. Lead compounds identified in a primary rat hepatocyte screen were shown to result in liver levels of NTP predictive of efficacy after intravenous dosing to rats. The oral bioavailability of the initial lead was below 5%; therefore, additional analogues were synthesized and screened for liver NTP levels after oral administration to rats. Addition of a 2‘,3‘-carbonate prodrug moiety proved to be a successful strategy, and the 1-(4-pyridyl)-1,3-propanyl prodrug containing a 2‘,3‘-carbonate moiety displayed oral bioavailability of 39%.